2019
DOI: 10.3126/jgmcn.v12i1.22618
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Outcome of Snakebite in Western Nepal: A Retrospective Study

Abstract: Introduction: Snakebite is an environmental hazard associated with significant morbidity and mortality. It is an important medical emergency and cause of significant numbers of hospital admissions in many parts of the Asian region. In this study, we assess the epidemiology and clinical outcome of snake bite. Methods: This was a retrospective study of all patients with snake bites admitted to the Department of Internal Medicine, Manipal Teaching Hospital, Pokhara, kaski, Nepal. A total numbers of 265 snak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…6,15,19 However other study from Western Nepal revealed green snake to be most prevalent. 9 Most of the people was bitten during sleep or early morning between 12am to 6am in this study which is similar to the study done in India. 6,20 Another study from western Nepal the maximum bites were between 5 to 7am which is also similar to our finding.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…6,15,19 However other study from Western Nepal revealed green snake to be most prevalent. 9 Most of the people was bitten during sleep or early morning between 12am to 6am in this study which is similar to the study done in India. 6,20 Another study from western Nepal the maximum bites were between 5 to 7am which is also similar to our finding.…”
Section: Discussionsupporting
confidence: 88%
“…Snakes habitats, holes are flooded by water and they hide in the houses, bushes, fields where they encounter humans. 9,10,18 Krait was the most prevalent snake among the identified one, a larger number of snakes remain unidentified and unknown. This is due to the bite occuring during sleep or due to the lack of awareness among the general public about the type of snake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,10 The common symptoms reported due to snakebite in these regions include local site pain, swelling with local tissue damage, and haematological features like coagulopathy, hematuria and thrombocytopenia. [11][12][13] Attempts to manage these symptoms have been done with Government supplied polyvalent antisnake venom for venom neutralization, vitamin K and Fresh Frozen Plasma (FFP) injection for coagulopathy management, MgSO 4 dressing and antibiotics for local manifestations of the snakebite and solely conservative management has been done at the centres with no availability of anti-snake venom. [11][12][13] Complications like severe coagulopathy, intrauterine foetal demise, and renal failure have been reported in studies from other countries.…”
Section: Clinical Outcomes Of Snakebites In Hills and Mountains Of Nepalmentioning
confidence: 99%